Expectations of outcomes in patients with colorectal cancer. Issue 5 (10th May 2018) - Young, A L; Lee, E; Absolom, K; Baxter, H; Christophi, C; Lodge, J P A; Glaser, A G; Toogood, G J
Abstract: Background: Understanding patients' expectations of their treatment is critical to ensure appropriate treatment decisions, and to explore how expectations influence coping, quality of life and well-being. This study aimed to examine these issues related to treatment in patients with colorectal cancer. Methods: A literature search from January 1946 to September 2016 was performed to identify available data regarding patients' expectations of outcomes following colorectal cancer treatment. A narrative synthesis of the evidence was planned. Results: Of 4337 items initially identified, 20 articles were included in the review. In studies presenting data on overall and short-term survival, patients considerably overestimated prognosis. Patients also had unrealistic expectations of the negative aspects of chemotherapy and stomas. There was marked discordance between patients' and clinicians' expectations regarding chemotherapy, end-of-life care, bowel function and psychosocial outcomes. Level of education was the most consistent factor influencing the accuracy of patients' expectations. Conclusion: Patients with colorectal cancer frequently have unrealistic expectations of treatment. Marked disparities exist between patients' and clinicians' expectations of outcomes. Graphical Abstract: A scoping review of the literature regarding colorectal cancer patients' expectations of the outcomes of their treatment. The main findings discussed are the overestimation of patients' expectations of prognosis and the discordance between patients' and clinicians' expectations of outcome. Marked differences between expectations of clinicians and patients